The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.14719/pst.2014.1.3.56
|View full text |Cite
|
Sign up to set email alerts
|

Smart-use of fertilizers to manage spider mites (Acari: Tetrachynidae) and other arthropod pests

Abstract: Fertilizers are utilized to increase productivity through improved crop growth and yield potential. However, steady declining availability of synthetic fertilizers is becoming a growing concern to the World's food production industry. At the same time, there is increasing evidence that non-optimal (not applied at the right time and either at too high or too low dosages) applications of fertilizers may adversely affect the biochemical, physiological and morphological characteristics of crop plants, which in tur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 27 publications
(41 reference statements)
0
6
0
Order By: Relevance
“…Potassium deficiency can lead to limited growth, metabolism, and stress defense (Wang et al, 2013). Plants that have potassium deficiencies are more susceptible to pest damage (Wang et al, 2013; West & Nansen, 2014). Our results show that organic GC enhances available potassium in peach orchards boosting the crop defense against pests.…”
Section: Discussionmentioning
confidence: 99%
“…Potassium deficiency can lead to limited growth, metabolism, and stress defense (Wang et al, 2013). Plants that have potassium deficiencies are more susceptible to pest damage (Wang et al, 2013; West & Nansen, 2014). Our results show that organic GC enhances available potassium in peach orchards boosting the crop defense against pests.…”
Section: Discussionmentioning
confidence: 99%
“…Plants deficient in K exhibit limited growth, metabolism and stress defence (Wang et al 2013) which leads to lower yield and quality of grain and hay. Due to these factors, there is growing scientific support that K-deficiency in plants allows for increased performance of herbivorous arthropods (Wang et al 2013;West and Nansen 2014) which further stresses plants and diminishes yields and quality. Information regarding the effects of K-deficiency on the performance of economically important arthropod pests would benefit agricultural production specialists by emphasizing the importance of K nutrition, not just for optimal growth but also for plant defence against key arthropod pests and diseases.…”
Section: Introductionmentioning
confidence: 99%
“…It is possible that these changes in nutrient concentration were coincidental to the aphid preference, as there are other factors, including soluble carbohydrates and amino acids, which have also been linked to aphid performance (Hu et al 2014). Although the direct link between these elements and aphid preference and performance were not established in this work, numerous studies have demonstrated the importance of potassium regarding pest infestations of crops (West and Nansen 2014 analysis and showed that, among the main nutritional elements, leaf potassium content showed the strongest negative correlation with spider mite (Acari: Tetranychidae) bio-response. This result is corroborated by a review of >2,000 studies regarding effects of potassium on pest and disease incidence in plants, in which Perrenoud (1990) found that in 63% of these studies, application of potassium led to a decrease in pest pressure.…”
Section: Discussionmentioning
confidence: 81%